Runner and gating design handbook : tools for successful injection molding - Beaumont, John P., 1952- (Hanser Publishers ; Hanser Publications, 2019)
"For the first time, both the art and the science of designing runners and gates are presented in a concise format. Tried and true runner and gating design techniques successfully used with various materials and molding applications are described together with cutting edge new technologies. The book will help readers determine when to use what type of runner system and how to isolate molding problems generated by the gate and runner vs. other molding issues. Much emphasis is placed on the critical features in a hot runner design and how to determine what type of design is best for a specific application. Finally, readers will be able to separate the sales hype from reality when dealing with hot runner suppliers. Contents Overview of Runners, Gates, and Gate Positioning Rheology of Plastics Filling and Packing Effects on Material and Molded Part Gate Positioning and Molding Strategies The Melt Delivery System Filling and Melt Imbalances Developed in Multi-Cavity Molds Runner Layouts Managing Shear-Induced Melt Variations for Successful Molding Cold Runner Molds Hot Runner Molds Hot Runner Flow Channel Design Hot Runner Drops, Nozzles, and Gates Thermal Issues of Hot Runner Systems The Mechanics and Operations of Hot Runners Process of Designing and Selecting a Runner System Troubleshooting"--
Keywords: vstřikování plastů; vstřikovací zařízení; vtokové soustavy; tváření plastů; injection moulding; injection systems; runner systems; plastic moulding; příručky; handbooks and manuals